Tindak Pidana Terorisme Berdasarkan Perspektif Belom Bahadat - citranu, citranu (Satya Dharma : Jurnal Ilmu Hukum, 2020)
This article purpose to examine Belom Bahadat's perspective of terrorism. The existing problems are examined using the normative legal writing method through a doctrinal approach, statutory approach and conceptual approach. The result of this study is the criminal act of terrorism is an extraordinary crime and contrary to the principle of Belom Bahadat, the perpetrators of terrorism can be prosecuted and tried under the adat Dayak Ngaju criminal law in this case Article 96 of the Tumbang Anoi 1894 Peace Agreement, not only terrorism but also the perpetrators spreaders or actors who carry out radicalism and extremism that are in the area of ​​ adat Dayak Ngaju law can already be considered to violate adat Dayak Ngaju law in this case the Belom Bahadat principle. Belom Bahadat perspective of terrorism Prevention can be done by deepening the meaning of Huma Betang and the life goals of Penyang Hinje Simpei.